Runoff estimation and the potential sites for water harvesting in central Butana rangeland, Sudan (2006 – 2007) - Ahmed Elfaki, Elsadig; Adeeb Mohamed, Ali; Saïdi3, Slim; Ickowicz, Alexandre (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
Estimation of direct surface runoff in a watershed is necessary for planning, designing and environmental impact analysis of water resources management projects.  The standard soil conservation service – curve number is a versatile and widely used procedure for runoff estimation. This model computes direct runoff through empirical equations that requires rainfall and a watershed coefficient data. The watershed coefficient, known as the runoff curve number (CN), represents the runoff potential of the land cover soil complex. Butana rangeland is located in eastern Sudan and considered as one of the best grazing areas in central Sudan. Due to rain variability and uneven distribution of rains, the area suffers from severe shortage of water which is reflected on the quantity and quality of biomass production and drinking water. The runoff potential of the central Butana rangeland was evaluated and assessed, during the rainy season of 2006 -2007,  through curve number model for better management of this rangeland which faces severe water shortage problem during the dry season. This potential of runoff water can be harvested either in the soil profile to improve biomass production or can be stored in artificial ponds for supplementary irrigation and drinking water. Rainfall data, as input, was taken from six rain gauges installed in this area. Landform, drainage pattern, slope, vegetation and land use/land cover were precisely mapped by the mean of perpendicular vegetation  vegetation index (PVI), calculated from Spotview satellite scene and field survey data, and digital elevation model data. Soil units were digitized and saved in GIS database and intersected with other watershed characteristics. The model was run and the result shows big variation of runoff depths, but the average potential runoff depth in the study area, which covers 3600 km 2 , was found 52 mm yr -1 . Hence, the total runoff volume was estimated for the whole study area as 187.2 x 10 6 m 3 annually. The watershed delineation and drainage routes, derived from digital elevation data, show the appropriate sites to construct water harvesting structures.